Contribution of developed countries towards MOOCs: an exploration and assessment from a representative platform Coursera. Issue 2 (7th September 2020) - Ayoub, Arshia; Amin, Raashida; Wani, Zahid Ashraf
Abstract : Purpose: The recent spate of eminence received by the MOOCs (massive open online courses) from media to academia is revolutionary in higher education. MOOCs are a disruptive technological innovation which offers open learning with the aid of the internet and delivered by the faculty of reputed institutions, globally. Since Coursera being one such significant platform, its exploration would display the broader picture of MOOCs. As a result, studying it from various dynamics has been the motive of the current endeavour. Design/methodology/approach: The quantitative study of the collected data was applied with help of descriptive research methodology to measure the contribution of the top six countries namely US, China, Japan, Germany, India and UK. All these six countries were selected on the basis of GDP (harvested from official website World Bank – data.worldbank.org/ to Coursera––an online platform providing MOOCs. The involvement of these selected countries was gauged (from the official website of Coursera https://www.coursera.org/ ) in terms of number, type of contributing institutions, number of courses offered by those institutions, type of courses offered, number of instructors and instructor gender ratio. Findings: The findings reveal that the United States (US) is the top contributor in terms of partner institutes (97), courses (Specialization courses – 1, 267 and degree courses– 40) and number of instructors (1, 290). Interestingly, it was also observed that universities are the major contributor institutes in all six studied countries. Most of the institutes provide specialization courses while a very few provide degree courses. A large number of instructors are involved for imparting these courses online. Instructor gender ratio on average is 2:1 (male: female). It was also observed that there is usually a specific common time of starting courses on Coursera. Originality/value: Online platforms are the main delivery points for MOOCs; therefore, vibrancy and articulacy of such platforms make this innovation a success, and examining such a platform which exhibits such characteristics would present an overall picture of its functionality, development, evolution and future expansion of the innovation (MOOCs).